DETERMINAN TAX AVOIDANCE PADA PERUSAHAAN FOOD AND BEVERAGES DI INDONESIA - Andri Sjahputra (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
This study aims to determine the effect of accounting conservatism and inventory intensity on tax avoidance in manufacturing companies of food and beverages listed on the Indonesia Stock Exchange for the period 2013-2017. The population in this study were food and beverages companies listed on the Indonesia Stock Exchange in the period of 2013 to 2017 as many as 21 companies. The type of research used in this study is associative - quantitative research. The data used in this study are secondary data obtained from the annual financial statements of manufacturing companies in the food and beverages sector which are listed on the Indonesia Stock Exchange (IDX) through the site www.idx.co.id. Sampling using purposive sampling method and obtained 40 financial report data manufacturing companies in the food and beverages sector that meet the criteria. Data were analyzed using a multiple linear regression analysis model and using SPSS version 24. The results of the study showed that simultaneously Accounting Conservatism and Inventory Intensity had an effect on Tax Avoidance. And partially, the two independent variables, including Accounting Conservatism and Inventory Intensity, influence Tax Avoidance